A CONCEPTUAL FRAMEWORK ON THE ASSESSING FACTORS THAT INFLUENCE THE EFFECTIVENESS OF CASHLESS AMONG UITM STUDENTS IN KOTA BHARU - Ab Rahman, Siti Maziah; Ghazali , Siti Aswani; Nawawi , Rabihah; Ab Rahman , Hasnuddin; Md Nor , Nor Haryanti; Mohd Aznan , Nadia Farleena; Nik Muhammad Naziman , Yusrina Hayati (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to develop a conceptual framework to identify the factors that influence the effectiveness of cashless usage among students at Universiti Teknologi MARA (UiTM). In today's digital era, cashless payment systems are gaining ground as a more efficient and secure alternative to cash payments. However, the level of effectiveness of using this system among students is still not clear. This quantitative study will focus on several key factors such as technological awareness, ease of use, security, and infrastructure support. Data will be collected through a questionnaire distributed to UiTM students. Statistical analysis will be used to identify the relationship between these factors and the effectiveness of using the cashless system. The results of this study are expected to provide guidance to educational institutions in empowering cashless payment systems and understanding the factors that contribute to its acceptance among students.